Relationship between Multidimensional Poverty Indicators and Health Behaviors among Turkish Children - Emre Özcan; Fikriye Yılmaz (İnsan & Toplum)
The aim of the study is to investigate the relationship between multidimensional poverty indicators and health behaviors among Turkish children. The sample of the study was determined to include at least one school from each socioeconomic status group in the districts of Ankara, which are classified into four socioeconomic groups, and the data were collected by applying face-to-face questionnaires to a total of 4,276 children, 2145 boys and 2136 girls, between the ages of 10 and 14. The data were analyzed using descriptive statistics, chi-squared test and binary logistic regression in the PASW Statistics program. The most striking results of the analysis showed that the female children, 5th, 6th, and 7th grade students, those who rated their health as good, those with a high or medium family affluence levels, those who were not deprived according to the Child Deprivation Index, those who rated their family income level as high or medium, and those who never suffered from hunger were more likely to be in the group with healthy behaviors (p<0.05). Accordingly, some school-based interventions and policies to be implemented in the family medicine system are recommended to promote the healthy behaviors of children, especially those living in poverty.